Réponses

2014-03-22T11:40:46+01:00
X/2+3=1
on multiplie par 2
x+6=2
x=2-6
x=-4

2/3 x-1=4
on multiplie par 3
2x-3=12
2x=15
x=15/2

15-x/4=2
on multiplie par 4
60-x=8
x=60-8
x=52

3x+2=x-10
3x-x=-10-2
2x=-12
x=-12/2
x=-6

2x-5=5x+1
5x-2x=-5-1
3x=-6
x=-6/3
x=-2
Meilleure réponse !
  • Utilisateur Brainly
2014-03-22T11:54:18+01:00
Résolution:

x/2 + 3 = 1
x/2 = -2
x= -4

2/3x -1 = 4
2/3x = 5
x = 15/2

15 -x/4 = 2
-x/4 = -13
-x = -52
x = 52

3x+2 = x -10
2x = -12
x = -6

2x -5 = 5x +1
-3x = 6
x = -2

Voilà ! J'espère t'avoir aidé(e) ! :)